Dependence of harmonic generation on primary wave pressure distribution - Baranowska, Anna (Archives of Acoustics, 2007)
The aim of this paper is theoretical analysis of harmonic generation during finite amplitude wave propagation. The paper presents mathematical model and some results of numerical calculations. The mathematical model was built on the basis of the KZK equation. To solve the problem the Fourier series expansion and finite-difference method were applied. The harmonic pressure amplitudes as a function of axial distance and their transverse distributions at fixed distances from the source were examined. The pressure amplitude distributions at horizontal section were investigated, too. The calculations were carried out for different pressure distributions on the circular source and different values of medium parameters.